2012
DOI: 10.1071/mf12211
|View full text |Cite
|
Sign up to set email alerts
|

Larval anisakid nematodes in teleost fishes from Lizard Island, northern Great Barrier Reef, Australia

Abstract: A survey was undertaken to characterise larval anisakid nematodes present in teleosts at Lizard Island on the northern Great Barrier Reef. In total, 464 fish were examined from 32 families, 62 genera and 107 species. Anisakid nematodes were found in 46 (9.9%) of the fish examined. Infections in Atherinidae, Lethrinidae, Lutjanidae and Serranidae were moderately prevalent, with the intensities of infection ranging from 1 to 80; whereas in the Sphyraenidae and Scombridae, the prevalence of infection was very hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Based on morphological characteristics observed using both light and scanning electron microscopy, L3 anisakid larvae in the present study were morphologically similar to previous specimens studied [19,22,[26][27][28][29][30]. For example, a distinct boring tooth and undeveloped lips at the anterior end of larva, the position of the excretory pore at the base of ventrolateral lips below the boring tooth and the rounded tail with a mucron were similar to those previously described [31].…”
Section: Discussionsupporting
confidence: 87%
“…Based on morphological characteristics observed using both light and scanning electron microscopy, L3 anisakid larvae in the present study were morphologically similar to previous specimens studied [19,22,[26][27][28][29][30]. For example, a distinct boring tooth and undeveloped lips at the anterior end of larva, the position of the excretory pore at the base of ventrolateral lips below the boring tooth and the rounded tail with a mucron were similar to those previously described [31].…”
Section: Discussionsupporting
confidence: 87%
“…The larvae have been found in scombrids and carangids such as Auxis thazard thazard and Thunnus thynnus from Brazil (SW Atlantic); Scomber japonicus and Trachurus picturatus from the NE Atlantic off Madeira; Euthynnus affinis, Scomberomorus commerson, Sarda orientalis and C. hippurus from the west Indian Ocean off Somalia; and from Merluccius merluccius from the eastern Mediterranean Sea . Further records were provided by Mattiucci et al (2005) from Florida, Farjallah et al (2008) from the Mediterranean coast of North Africa (Scomber scombrus, M. merluccius, Phycis phycis), from Australia by Cannon (1977) and more recently by Shamsi (2007Shamsi ( , 2014 and Jabbar et al (2012) from the Great Barrier Reef, and by Chen & Shih (2015) from Taiwan. Kuhn et al (2013) have already summarized the worldwide known hosts for genetically confirmed worms, naming 26 different teleost species.…”
Section: Hosts and Life Cyclementioning
confidence: 99%
“…Critical for the identification of worms to the species level is the use of reliable genetic markers. The first and second internal transcribed spacers (ITS-1 and ITS-2, respectively) of nuclear ribosomal DNA have proven useful for the specific or genotypic identification of many anisakids [31,32]. The sequence differences between or among species is usually much higher than variation within species [33].…”
Section: Molecular Identification and Classification Of Anisakidsmentioning
confidence: 99%
“…Six years later, the first clinical case of anisakiasis was reported in China [50]. Recent studies from Australasia also demonstrated prevalences of up to 100% for species including Neoplatycephalus richardson (tiger flathead) and Sillago flindersi (eastern school whiting) from temperate waters, and Scomberomorus commerson (narrow-barred Spanish mackerel) and Sphyraena forsteri (Bigeye barracuda) from tropical waters [27,31,35,36,51].…”
Section: Geographical and Host Distributionsmentioning
confidence: 99%